1998
DOI: 10.1002/(sici)1096-8628(19980526)77:4<277::aid-ajmg5>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Familial laryngeal paralysis

Abstract: Vocal fold paralysis (VFP) is the second most frequent cause of congenital stridor. Although often due to birth trauma, infection, and brainstem abnormalities, most cases are idiopathic. Infrequently, a family history of VFP is elicited, identifying a role for genetic factors in laryngeal function. This study describes a family in which an autosomal dominant form of familial laryngeal abductor paralysis segregates. The typical physical findings, diagnostic and therapeutic considerations, and possible molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This conclusion agrees with the conclusion of Berkowitz, who suggested that the cause of abCBILP might be an imbalance between abductor and adductor laryngeal muscles. Specifically, lesions of the nucleus ambiguous (anoxic, genetic) and a maturity delay in the motor unit might cause abCBILP …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion agrees with the conclusion of Berkowitz, who suggested that the cause of abCBILP might be an imbalance between abductor and adductor laryngeal muscles. Specifically, lesions of the nucleus ambiguous (anoxic, genetic) and a maturity delay in the motor unit might cause abCBILP …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, lesions of the nucleus ambiguous (anoxic, genetic) and a maturity delay in the motor unit might cause abCBILP. [31][32][33][34]…”
Section: Discussionmentioning
confidence: 99%
“…Very rarely, there is a clear pattern of familial transmission of laryngeal paralysis indicating that genetic factors play an important role in the development of normal laryngeal neuromuscular function. 2 Plott originally described familial bilateral abductor vocal fold paralysis in 1964. He reported three brothers with permanent congenital laryngeal abductor paralysis and mental retardation consistent with X-linked recessive inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…The family we studied displayed a dominantly inherited form of congenital laryngeal abduction paralysis, as previously described in a report by Manaligod and Smith. 7 In summary, 3 individuals in this family were identified who required tracheostomy soon after birth for bilateral vocal fold abductor paralysis. The propositus (individual 40) had absence of abduction of the vocal folds documented clinically and by laryngeal electromyography.…”
Section: Patients and Clinical Detailsmentioning
confidence: 99%
“…11,12 A second syndrome, Gerhardt syndrome, is a form of FLAP with autosomal dominant inheritance and variable penetrance and expressivity (Gerhardt syndrome, OMIM 150260). [13][14][15][16] Although mental retardation is not a common feature, 7 subtle central neurologic abnormalities can be demonstrated in some kindreds. 15 The finding of additional neurologic deficits and other malformations in conjunction with laryngeal abductor paralysis is common.…”
Section: Commentmentioning
confidence: 99%